Kajian Etnobotani Ajeruk Kopi di Kalisat Jampit sebagai Sumber Belajar Biologi pada Materi Keanekaragaman Hayati Kelas X SMA. - Qodril Ila, Izzata Barid; Nailul Istiqomah, Devi; Dewi, Rosita Fitrah (Education & Learning, 2026)
In ethnobotanical studies, local wisdom is frequently examined as traditional communities possess in-depth knowledge regarding the utilization of plants for daily needs, including medicinal, nutritional, constructional, and cultural purposes. This knowledge holds significant potential for integration into instructional materials to sustain cultural continuity and support locally grounded education. This qualitative study investigates the ethnobotanical potential of Ajeruk kopi in Kalisat Jampit and develops it into a biology learning resource for Grade X biodiversity material. A descriptive qualitative approach employing ethnobotanical methods was utilized in this research. The findings were translated into a leaflet as an instructional material, and expert validation indicated that the developed leaflet is feasible for use as a contextual biology learning resource. Ajeruk kopi demonstrates substantial potential as an engaging and relevant locally based learning resource for biodiversity instruction at the secondary education level.